PENGEMBANGAN DIRI DALAM STANDARDISASI DUNIA USAHA DAN INDUSTRI MELALUI KEGIATAN TALKSHOW - Dian Nugraha; Mohamad Zaenudin; Safira Faizah (Universitas Mataram, 2023)
In the era of fierce global competition, rapid changes within the business and industrial landscape present increasingly intricate challenges for students. Self-development at both academic and professional levels has become essential in shaping characters capable of navigating these dynamics. The significance of mastering hard skills, reinforced by ISO certification and national standards, is paramount. Enriching soft skills through holistic education and real-world practice is crucial to confront the dynamic work environment. Recognizing these imperatives, a talkshow was organized to delve into self-development and comprehend the importance of self-development in conjunction with the significance of standardization in the world of business and industry. Through an interactive format, the talkshow introduced the concept of self-development, identification of hard and soft skills, self-development practices, and adaptation to evolving standards and technologies in the workplace. This material was delivered by trainers from Makara UI Academy and the National Standardization Agency (BSN) of Indonesia. The outcomes of the talkshow portray significant positive effects, with a majority of participants experiencing a notable improvement in understanding the essential role of self-development and certification in enhancing competitiveness within the challenging realms of busineAss and industry. Attendees also demonstrated a heightened awareness of the urgency of self-development in achieving success in the complex domains of business and industry. These results reflect the profound impact of the knowledge imparted by speakers, propelling participants toward deeper understanding and readiness to face contemporary challenges in an increasingly dynamic professional environment. Shaping character and acquiring hard skills are essential in confidently confronting the dynamics of industry standards.